Answer:
7(3^2) + 2(3).
That equals to 7(9) + 2(3).
That equals to 63 + 6.
That finally equals to 69.
Step-by-step explanation:
Answer:For these, n is equal to the term you want. So you substitute the number in for whichever term you want. This means:
a) 1 (1st term) + 5 = 6
2 (2nd term) + 5 = 7
3 (3rd term) + 5 = 8
4 (4th term) + 5 = 9
10 (10th term) + 5 = 15
And so on for b (not going to keep writing the term, I’m sure you get that by now.
b) 2(1) - 1 = (2x1) - 1 = 1
2(2) - 1 = (2x2) - 1 = 3
2(3) - 1 = (2x3) - 1 = 5
2(4) - 1 = (2x4) - 1 = 7
2(10) - 1 = (2x10) - 1 = 19
Hope this helps :)
35m because 35 dollars multiplied by m months
Answer: e= 10
Step-by-step explanation:
Answer:
Q1 (-2,-5)(0,3)(4,19)(7,31)
Step-by-step explanation: